Website of the Health Office of PPKB (Population Control, and Family Planning) of Mojokerto City: Website Dinas Kesehatan PPKB (Pengendalian Penduduk , dan Keluarga Berencana) Kota Mojokerto - Nashrullah, Mochammad Daffa Khasifi; Suprianto, Suprianto (Procedia of Engineering and Life Science, 2024)
The use of information technology has become mandatory in the current digital era, followed by the increasingly widespread development of the internet, which has further strengthened the importance of a web- based system. In designing a website-based system, the Department of Health, Population Control and Family Planning creates a Health Information System, PPKB Program, or Population Statistics. With this system, it explains the importance of the PPKB Health Strategy, in information related to population in an interesting and easy to understand way, detailed information regarding available health services, the PPKB (Population Control and Family Planning) program, population policies, and the latest initiatives. Tools or Interactives that help users in planning a family or understanding population statistics. Responsive design that ensures the website can be accessed well on various devices, including mobile phones and tablets, and ensures accessibility for users with special needs such as health services, information, or adequate accessibility features such as clear actions for visitors to engage further, or such as register for the PPKB program, look for further health information or can join relevant events or campaigns. Integrate social media, video streaming or other latest technology to improve user order and distribute information more effectively. This website must be a valuable and reliable source of information for the residents of the city of Mojokerto, providing needed support in health, PPKB programs, and understanding population issues. The success of this website depends on its ease of use, relevance of content, and its ability to encourage positive actions from visitors.